2019
DOI: 10.1103/physrevlett.122.102501
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Incomplete Fusion Products and the Suppression of Complete Fusion in Reactions of Li7

Abstract: Above-barrier complete fusion involving nuclides with low binding energy is typically suppressed by 30%. The mechanism that causes this suppression, and produces the associated incomplete fusion products, is controversial. We have developed a new experimental approach to investigate the mechanisms that produce incomplete fusion products, combining singles and coincidence measurements of light fragments and heavy residues in 7 Li þ 209 Bi reactions. For polonium isotopes, the dominant incomplete fusion product,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…This suppression amounts up to ∼30% for these nuclei, is roughly independent of the target nucleus and is typically accompanied by significant yields of evaporation products compatible with the partial absorption * jinl@ohio.edu † moro@us.es of the projectile, also referred to as incomplete fusion, ICF. However, some recent experimental results [18] suggest that the ICF products are compatible with a direct, one-step mechanism, thus putting into question the BF picture.…”
mentioning
confidence: 99%
“…This suppression amounts up to ∼30% for these nuclei, is roughly independent of the target nucleus and is typically accompanied by significant yields of evaporation products compatible with the partial absorption * jinl@ohio.edu † moro@us.es of the projectile, also referred to as incomplete fusion, ICF. However, some recent experimental results [18] suggest that the ICF products are compatible with a direct, one-step mechanism, thus putting into question the BF picture.…”
mentioning
confidence: 99%
“…It has been in heavy demand for measurements that complement other HIAF research programs and for detector characterisation and development. For example, γ-ray angular distributions were measured following (p,p ) excitation of nuclei such as 12 C, and 50,52 Cr, complementing electron spectroscopy measurements with the Super-e that aim to determine electric monopole (E0) transition strengths between shape-coexisting nuclear states. Quenching factors for dark matter detector characterisation have been measured using neutrons produced by 7 Li(p,n) 7 Be as a proxy for a neutral dark matter particle inducing a nuclear recoil in a scintillator detector [6].…”
Section: Line 4: General Purposementioning
confidence: 99%
“…For polonium isotopes, the dominant incomplete fusion product, only a small fraction can be explained by projectile breakup followed by capture: the dominant mechanism is triton cluster transfer. Suppression of complete fusion is therefore primarily a consequence of clustering in weakly bound nuclei rather than their breakup prior to reaching the fusion barrier [52].…”
Section: Line C: Cube and Balinmentioning
confidence: 99%
“…It should be pointed out that there are some dedicated efforts and improvements in the PLATYPUS model (e.g., by taking into account lifetimes associated with unbound states) for the study of 6,7 Li-induced reactions. Also, studies have revealed the importance of transfer-triggered breakup [16][17][18] and cluster transfer [19]. However, studies have also shown that prompt breakup of 9 Be occurs dominantly through an excited 8 Be nucleus [10].…”
Section: Comparison Of Data With Theoretical Predictions and Dismentioning
confidence: 99%
“…Apparently, for the CF suppression the underlying mechanism is complicated and controversial. It is also reported to be affected by other processes such as transfer-triggered breakup [16][17][18] and cluster transfer [19].…”
Section: Introductionmentioning
confidence: 99%